The psychology of economic narratives: emotional asymmetry and the paradox of inflation forecasts - Zubiel, Magdalena; Lipowski, Mariusz; Szyszko, Magdalena; Springer, Agnieszka (Oeconomica Jadertina, 2025)
This paper investigates the influence of the emotional tone in expert commentary on inflation forecasts while keeping the informational content constant. Utilizing concepts from behavioural economics and cognitive psychology-specifically framing, anchoring, and the positive-negative asymmetry, the research presents the “inverse effect”, namely a counterintuitive pattern that increases inflation forecasts with reassuring commentary, whereas alarmist commentary decreases them. A between-subjects experiment was carried out involving 254 Polish university students chosen for their limited economic knowledge. Participants were randomly assigned to receive either positively or negatively toned commentary that was informationally equivalent, and they provided forecasts before and after the intervention. The data were analysed using nonparametric tests (Mann-Whitney U and Wilcoxon), with effect sizes reported. The results indicate that emotional framing has a significant effect on expectations. The negative tone had a more pronounced effect than the positive tone, aligning with the concept of affective asymmetry; however, the direction of the change was contrary to the initial hypotheses, thereby demonstrating the inverse effect. These results enhance the understanding of how economic communication can shape public perception without the introduction of new information, carrying implications for central banks, policymakers, and the media. Limitations of the study include the non-representative nature of the student sample, the laboratory setting, and the restricted measurement of individual differences. Future research should explore field settings, more diverse populations, and model-based methodologies to examine boundary conditions and confirm the inverse effect across different formats.